Advancements in AI-Based Process Control for Real-Time Industrial Applications - ., Aarti (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 3&4 (2024): Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
The adoption of artificial intelligence (AI) in industrial automation has enabled remarkable advancements in process control, allowing industries to improve productivity, precision, and efficiency. AI-driven process control systems, which include machine learning algorithms, predictive maintenance models, and real-time data analytics, have the potential to transform industrial applications. This article delves into the advancements in AI-based process control systems, with a focus on real-time applications, discussing key technologies, benefits, challenges, and future prospects in various industries, such as manufacturing, energy, pharmaceuticals, and automotive.